MENANGKAL RADIKAL BEBAS DENGAN ANTI-OKSIDAN - KHAIRA, KUNTUM (Sainstek : Jurnal Sains dan Teknologi, 2010)
This article aims at understanding free radical and how antioxidant can neutralize it. This reactive and unstable chemistry molecules could destruct cell. Free radical coul be formed automatically by respiration result or generate from external factor like air pollution, cigarette smoke, emition of vehicle or access of UV light. To stop free radical, it must be concerned seriously that the supply of antioxidant in our body is sufficient. Endogenus antioxidant must be added by exogenus antioxidant to make it react with free radical to produce stable molecules.Key words: free radical, antioxidant